Subacute bacterial endocarditis with vasculitis-like presentation; report of a case and literature review - Tayebeh Soleymanian; Hoda Kavosi (Society of Diabetic Nephropathy Prevention, 2020)
Infective endocarditis is a diagnostic challenge since it could manifest as a systemic disease mimicking rheumatologic disorders by immunological mechanisms. We introduced a case of infective endocarditis which was a 62-year-old man who presented with weakness, weight loss, myalgia, arthritis, petechiae, hematuria and proteinuria and was admitted by a rheumatologist for evaluation of possible vasculitis.